Implantation of Autologous Stem Cells Derived from Adipose Tissue in Rat Bone Fractures (International Journal of Medical and Surgical Sciences, 2014)
Stem cells derived from adipose tissue (ASCs) correspond to a major advance with respect to the bone regenerative medicine, as they have the ability for self-renewal, differentiation and paracrine stimulation to various types of tissues including bone and cartilage. The hypothesis of this study considers that fractures treated with ASCs, time decreases bone regeneration and vascularization increases, aiming to histologically evaluate bone regeneration and vascularization in these fractures. To accomplish this, 24 young male Sprague Dawley rats were used. The specimens were divided into two groups: Group A (treated) and group B (control). In both groups, the rats were euthanized at 11 and 21 days post-fracture. Statistically significant difference was observed in the number of newly formed trabeculae and vascular density in the treated group compared to control group concluded that rats treated with ASCs have a higher rate and better angiogenic bone regeneration, especially given the ability to synthesize components of the extracellular matrix of these cell, and the production of angiogenic growth factors.